Perineural dexamethasone reduces rebound pain after ropivacaine single injection interscalene block for arthroscopic shoulder surgery: a randomized controlled trial. Issue 11 (17th September 2021) - Woo, Jae Hee; Lee, Hyun Jung; Oh, Hye-Won; Lee, Jong Wha; Baik, Hee Jung; Kim, Youn Jin
Abstract : Background and objectives: A single injection interscalene block (ISB) is a common regional analgesic technique in patients undergoing arthroscopic shoulder surgery. However, rebound pain after ISB resolution may reduce its overall benefit. Our primary aim was to assess whether perineural dexamethasone reduces the intensity and incidence of rebound pain in patients undergoing arthroscopic shoulder surgery under general anesthesia combined with a preoperative single injection ISB. Methods: The patients were randomly assigned to receive single injection ISB using either 0.5% ropivacaine (control) or 0.5% ropivacaine containing 5 mg of dexamethasone. The primary outcomes were the pain score difference before and after ISB resolution, and the incidence of rebound pain. The secondary outcomes were the onset and duration of rebound pain, the presence of sleep disturbances due to postoperative pain, the first time when an analgesic was requested, and pain scores at various predefined time points. Results: Pain increase following ISB resolution was lower in the dexamethasone group compared with the control group (4.5±2.4 and 6.9±2.2, respectively, p<0.001). The incidence of rebound pain was significantly lower in the dexamethasone group compared with the control group (37.1% and 82.9%, respectively, p<0.001). The controls experienced greater sleep disturbance during the postoperative period compared with those who received ISB with perineural dexamethasone. Conclusions: Perineural dexamethasone added to ISB using ropivacaine led to a much smoother resolution of ISB, reflected in a significantly smaller increase in pain after block resolution, a lower incidence of rebound pain and a lower sleep disturbance during the first postoperative week. Trial registration number: Clinical Trial Registry of Korea (KCT0004418).